Land Productivity Enhancement by Sulfur Nutrient Management in Vertisol Rice Field - Kasno, Antonius; Anggria, L.; Rostaman, T. (AGRIVITA, Journal of Agricultural Science, 2017)
Sulfur is a secondary soil macro nutrients needed by plants as the most important part of the essential amino acids (cystine and methionine), protein synthesis, chlorophyll production and carbohydrate metabolism. The research aimed to study the land productivity improvement of Vertisol rice field by controlling the sulfur nutrient. The study was conducted in Dawu, Paron, and Guyung, Gerih, Ngawi, East Java, Indonesia, during the dry season 2013 and 2014. A randomized complete block design, with eight treatments and three replications were applied. The treatments were some rates of S-fertilizer application combined with in situ straw compost, ZA and Kieserit. Experimental plots dimension is 6 m x 5 m. Ciherang and Membramo were rice varieties grown in legowo 2:1 system. The results showed that S-fertilizer application can increase the weight of dry grain harvest and dry grain milled. The optimum doses of S-fertilizer were 24 kg S ha-1. Kieserit application resulted in less grain yield than ZA. Manure can increase the weight of dry grain harvest and tend to increase the weight of dry milled grain compared to those of the control treatments.